Pengaruh Pengaruh Return on Assets dan Debt to Equity Ratio Terhadap Return Saham Perusahaan IDX30 di Bursa Efek Indonesia - Muhammad Sidik; Idham Lakoni; Markoni Markoni (Journal of Business and Economics Research (JBE), 2023)
This study aims to determine the effect of return on assets (X1) and debt to equity ratio (X2) on stock returns (Y) with the analytical method using, multiple linear regression, multiple correlation, determination, t test and F test. The data used in this study is secondary data derived from the IDX30 company's annual report on the Indonesia Stock Exchange. According to the results of the multiple linear regression test, the equation Y = –0.165 + 1.416 X1 – 0.019 X2 is obtained. From the results of the multiple correlation test, the value (R) = 0.374 is in the coefficient interval of 0.20 - 0.399, meaning that there is a low correlation between the variable return on assets (X1) and the debt-to-equity ratio (X2) to stock returns (Y). From the test results of the coefficient of determination, the value of R2 = 0.113 or (11.3%) means that together return on assets (X1) and debt to equity ratio (X2) contribute to stock returns (Y) of R2 0.113 or (11.3%) while 88.7% is influenced by other variables not examined in this study. From the results of the t test, the calculated t value of return on assets (X1) is 2.248 with α = 0.028 smaller than α = 0.05 meaning that return on assets (X1) has a significant effect on stock returns (Y). The t value of the debt-to-equity ratio (X2) is -0.572 with α = 0.569 greater than α = 0.05 meaning that the debt-to-equity ratio (X2) has no effect on stock returns (Y). From the test results Fcount is 5.129 with α = 0.009 smaller than α = 0.05 means that Ha is accepted. Then simultaneously return on assets (X1) and debt to equity ratio (X2) have a significant effect on stock returns (Y).